Associations of decadal to multidecadal sea-surface temperature variability with Upper Colorado River flow - McCabe, Gregory J.; Betancourt, Julio L.; Hidalgo León, Hugo G. (JAWRA Journal of the American Water Resources Association, 2007)
The relations of decadal to multidecadal (D2M) variability in global sea-surface temperatures (SSTs) with D2M variability in the flow of the Upper Colorado River Basin (UCRB) are examined for the years 1906- 2003. Results indicate that D2M variability of SSTs in the North Atlantic, North Pacific, tropical Pacific, and Indian Oceans is associated with D2M variability of the UCRB. A principal components analysis (with varimax rotation) of detrended and 11-year smoothed global SSTs indicates that the two leading rotated principal components (RPCs) explain 56% of the variability in the transformed SST data. The first RPC (RPC1) strongly reflects variability associated with the Atlantic Multidecadal Oscillation and the second RPC (RPC2) represents variability of the Pacific Decadal Oscillation, the tropical Pacific Ocean, and Indian Ocean SSTs. Results indicate that SSTs in the North Atlantic Ocean (RPC1) explain as much of the D2M variability in global SSTs as does the combination of Indian and Pacific Ocean variability (RPC2). These results suggest that SSTs in all of the oceans have some relation with flow of the UCRB, but the North Atlantic may have the strongest and most consistent association on D2M time scales. Hydroclimatic persistence on these time scales introduces significant nonstationarity in mean annual streamflow, with critical implications for UCRB water resource management. Universidad de Costa Rica//UCR/Costa Rica UCR::Vicerrectoría de Investigación::Unidades de Investigación::Ciencias Básicas::Centro de Investigaciones Geofísicas (CIGEFI)